Institutional structure of public finance law - TSINDELIANI, Mannep A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe article deals with actual problems of the institutionalization of the modern Russian financial law as a branch of law. The problems of the modern concept of the subject of the financial law of the Russian Federation and the construction of financial law on institutional and pandemic systems are investigated. Approaches for the allocation in the financial law system of such entities as fiscal law and the issue law, and the right of monetary circulation, the rights of public revenues are presented. In conclusion, the author's presentation to the system of the financial law of Russia is given. RESUMENEl artículo trata problemas reales de la institucionalización de la ley financiera rusa moderna como una rama de la ley. Se investigan los problemas del concepto moderno del tema del derecho financiero de la Federación de Rusia y la construcción del derecho financiero sobre los sistemas institucionales y pandémicos. Se presentan enfoques para la asignación en el sistema de derecho financiero de entidades tales como la ley fiscal y la ley de emisión, y el derecho de circulación monetaria, los derechos de los ingresos públicos. En conclusión, se presenta el autor al sistema de derecho financiero de Rusia.